Data supporting 'Public perceptions of household IoT smart water ‘event’ meters in the UK – implications for urban water governance' - Shannon, Caitriona; Smith, Heather M. (Cranfield University, 2022)
Student project collecting quantitative data on the UK public perceptions around water consumption and smart meters in the home, using an online survey.Data was collected through Qualtrics (n=558) from 20th - 24th July 2020. Files require SPSS software to be opened. Please contact if another format is required.
Keywords: Smart meter'; 'consumption'; 'perceptions'; 'wastewater'; 'water'; 'conservation'; 'behaviour'; 'Environmental Science and Management not elsewhere classified'; 'Environment and Resource Economics'